General Form of a Nonmonotone Line Search Technique for Unconstrained Optimization - Yu, Zhensheng; Lin, Ji (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2009)
By using the forcing function, we propose a general form of nonmonotone line search technique for unconstrained optimization. The technique includes some well known nonmonotone line search as special cases while independent on the nonmonotone parameter case. We establish the global convergence of the method under weak conditions and we report numerical test results with a modified BFGS method to show the effectiveness of the proposed method.